Implementasi manajemen risiko komprehensif pada perbankan syariah di Indonesia menuju budaya risiko positif dan responsif - Aprilian, Rifky Zahrul (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the implementation of risk management in sharia banking in Indonesia. The research method used is a literature review which uses related articles as research reference sources. This article comprehensively discusses the steps taken by sharia banking by adopting XYZ sharia bank in facing various risks, including market, credit, operational and sharia risks. By implementing appropriate policies, procedures and limits, as well as through active supervision by the Board of Commissioners, Directors and Sharia Supervisory Board, BSI aims to create a positive and responsive risk culture. Periodic evaluation of the effectiveness of risk management is also carried out to ensure effective and sustainable risk management.